Improving the Reliability of DC-DC Power Supply by Reserving Feedback Signals - V. A. Shpenst; E. A. Orel (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2021)
The paper deals with the problem of improving the reliability of DC-DC power supplies with pulse-width modulation. The topicality of the work is related to the importance of power supply issues in modern electronics, since the quality of operation of consumer electrical appliances, including critical ones, directly depends on the serviceability of sources. The object of the study is feedback circuits aimed at stabilization of the parameters of power supply of consumers. Failures of the mentioned feedback circuits most often occurs due to the electronic components degradation under harsh operating conditions as well as under severe mechanical overloads. Such failures are dangerous for uncontrolled increase of power supply output voltage and output current. To avoid this, a new method of reserving voltage feedback signals is presented in the paper which is implemented on the basis of flyback supply topology. Feedback signals are formed from the optocoupler located on the load side and from the auxiliary winding of the power transformer, together forming two independent output voltage control circuits. Only one circuit performs stabilization at any given moment of time. If one of these circuits fails, the second one can simply replace it in its operation. The proposed method does not require any digital signal processing algorithms or microprocessor control modules and can be implemented on the basis of cheap, widely available analog chips that perform pulse-width control of the output voltage. As a result, the problem of sudden feedback loop failure is solved and the reliability of electrical equipment is increased. The validity of the proposed method is confirmed by the results of computer simulation with the use of MatLab-Simulink environment. The obtained results can be used in design of fault-tolerant secondary power supplies that operate in harsh operating conditions.